The Impact of Different Types of Permeable Pavement Utilization on Air Temperature and Building Energy Consumption - Andika Citraningrum (RUAS (Review of Urbanism and Architectural Studies), 2012)
Pavements are found to be a significant contributor to the urban heat island. One of the strategies to mitigate it is by using permeable pavement. The purpose of this study is to investigate the impact of utilization of permeable pavement on air temperature above the pavement and building energy consumption. Simulation on five types of pavement (dense grade asphalt concrete/DGAC, permeable asphalt concrete/PAC, concrete, permeable interlocking concrete block/PICB, and grass block) using DesignBuilder software with concrete as the base for comparison shows that PICB has the highest air temperature reduction and energy consumption reduction compared to other type of pavements.Keywords: Permeable pavement, air temperature, energy consumption, DesignBuilder